Food provisioning in complex societies : zooarchaeological perspectives - Atici, Levent; Arbuckle, Benjamin S. (University Press of Colorado, 2023)
"Offers new insight into the mechanisms involved in food provisioning for complex societies. Combining zooarchaeological and historical data from global case studies to analyze patterns in centralization and bureaucratic control, asymmetrical access and inequalities, and production-distribution-consumption dynamics of urban food provisioning and animal management"--